Sargassum fusiforme Polysaccharide Rejuvenat es the Small Intestine in Mice Through Altering its Physiol ogy and Gut Microbiota Composition - Chen, P.; Yang, S.; Hu, C.; Zhao, Z.; Liu, J.; Cheng, Y.; Wang, S.; Chen, Q.; Yu, P.; Zhang, X.; Wu, M. (Current Molecular Medicine, 2017)
Background and Objective: Aging can result in a progressive decline in cellular protection and physiological function. The physiological status and microbiota of the intestine are intensively linked to the aging process. Numerous studies have suggested that Sargassum fusiforme polysaccharides possess antioxidant and antiaging activities. However, it remains unclear as to whether S. fusiforme polysaccharides can prevent the insult of oxidant and aging through modulating the physiological status and microbiota of the intestine. Methods: To assess the cytoprotective effect of S. fusiforme polysaccharides (SFPS) in the small intestine of mice embarking on the aging process, we compared the expressions of Nrf2 and several representative markers (SOD-2, CAT, NQO1 and HO-1) of the Nrf2/ARE signaling pathway in the small intestine of male ICR mice fed with a control diet with those of mice fed with a SFPS-containing diet. In addition, the overall compositional changes in the small intestine microbiota were determined by 16s rDNA sequencing followed by alpha and beta diversity analyses. Results: The results showed that dietary intake of SFPS could ameliorate the declined cytoprotective capacity of the small intestine by upregulating the Nrf2/ARE signaling pathway. Moreover, SFPS could partially rejuvenate the overall status of the small intestine microbiota. Conclusion: The results suggested that dietary SFPS may promote the health condition of the small intestine, consequently leading to a healthy aging.
Keywords: small intestine